Clavicle Fracture And Dissociation Clinical Radiological In The Newborn: Case Report - Quispe-Condori, Custodio Olsen (2015)
The clavicle fracture is the most common bone lesion of the newborn. The risk factors are: obstetric, maternal and fetal. The clinical manifestations of the clavicle fracture are more evident at the second and third day of life his diagnostic requires of one radiological confirmation; sometimes the requested radiography does not contribute to confirm the diagnosis of fracture of clavicle despite evident clinical picture. This is known as the clinical radiological dissociation. The management of fractured clavicle should be started as soon as you have done the clinical diagnosis and keep in mind that the radiographic plate is an auxiliary examination that is to say not always going to appreciate the bone lesion. It is important to assess the expertise of the evaluator in the decision making. A case is presented of a newborn eutocic delivery with clavicle fracture and dissociation clinical radiological. The present work realized in the Instituto Nacional Materno Perinatal by objective to contribute to medical knowledge and exchanging experiences in the diagnosis and management a newborn with fracture clavicle and dissociation clinical radiological.